Fictional Practices of Spirituality I Interactive Media - Marcato, Leonardo; Schniz, Felix (Edition Kulturwissenschaft, 2023)
»Fictional Practices of Spirituality« provides critical insight into the implementation of belief, mysticism, religion, and spirituality into worlds of fiction, be it interactive or non-interactive. This first volume focuses on interactive, virtual worlds - may that be the digital realms of video games and VR applications or the imaginary spaces of life action role-playing and soul-searching practices. It features analyses of spirituality as gameplay facilitator, sacred spaces and architecture in video game geography, religion in video games and spiritual acts and their dramaturgic function in video games, tabletop, or LARP, among other topics. The contributors offer a first-time ever comprehensive overview of play-rites as spiritual incentives and playful spirituality in various medial incarnations.